Twisting: Incidence and Risk Factors of an Intraprocedural Challenge Associated With Pipeline Flow Diversion of Cerebral Aneurysms. Issue 1 (13th July 2020) - Bender, Matthew T; Young, Robert W; Zarrin, David A; Campos, Jessica K; Caplan, Justin M; Huang, Judy; Tamargo, Rafael J; Lin, Li-Mei; Colby, Geoffrey P; Coon, Alexander L
Abstract: BACKGROUND: Pipeline Embolization Device (PED; Medtronic) "twisting" manifests with the appearance of a "figure 8" in perpendicular planes on digital subtraction angiography. This phenomenon has received little attention in the literature, requires technical precision to remediate, and has potential to cause ischemic stroke if not properly remediated. OBJECTIVE: To report incidence, risk factors, and sequelae of PED twisting and to discuss techniques to remediate a PED twist. METHODS: Case images were reviewed for instances of twisting from a prospectively-maintained, Institutional Review Board-approved cohort of patients undergoing flow diversion for cerebral aneurysm. RESULTS: From August 2011 to December 2017, 999 PED flow diverting stents were attempted in 782 cases for 653 patients. A total of 25 PED twists were observed while treating 20 patients (2.50%, 25/999). Multivariate analysis revealed predictors of twisting to be: Large and giant aneurysms (odds ratio (OR) = 9.66, P  = .005; OR = 27.47, P  < .001), increased PED length (OR = 1.14, P  < .001), and advanced patient age (OR = 1.07, P  = .002). Twisted PEDs were able to be remediated 75% of the time, and procedural success was achieved in 90% of cases. PED twisting was not found to be a significant cause of major or minor complications. However, at long-term follow-up, there was a trend towards poor occlusion outcomes for the cases that encountered twisting. CONCLUSION: Twisting is a rare event during PED deployment that was more likely to occur while treating large aneurysms with long devices in older patients. While twisting did not lead to major complications in this study, remediation can be challenging and may be associated with inferior occlusion outcomes. Graphical Abstract: